Complete genome sequence of Catenulispora acidiphila type strain (ID 139908T). Issue 2 (September 2009) - Copeland, Alex; Lapidus, Alla; Glavina Del Rio, Tijana; Nolan, Matt; Lucas, Susan; Chen, Feng; Tice, Hope; Cheng, Jan-Fang; Bruce, David; Goodwin, Lynne; Pitluck, Sam; Mikhailova, Natalia; et al.
Abstract Catenulispora acidiphila Bustiet al. 2006 is the type species of the genusCatenulispora, and is of interest because of the rather isolated phylogenetic location it occupies within the scarcely explored suborderCatenulisporineae of the orderActinomycetales .C. acidiphilia is known for its acidophilic, aerobic lifestyle, but can also grow scantly under anaerobic conditions. Under regular conditions, C. acidiphilia grows in long filaments of relatively short aerial hyphae with marked septation. It is a free living, non motile, Gram-positive bacterium isolated from a forest soil sample taken from a wooded area in Gerenzano, Italy. Here we describe the features of this organism, together with the complete genome sequence and annotation. This is the first complete genome sequence of the actinobacterial familyCatenulisporaceae, and the 10, 467, 782 bp long single replicon genome with its 9056 protein-coding and 69 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.